EPCT-16. A PHASE IB STUDY OF PTC596 IN CHILDREN WITH NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA AND HIGH GRADE GLIOMA. (4th December 2020) - Smiley, Natasha Pillay; Baxter, Patricia; Kumar, Shiva; Hwang, Eugene; Breneman, John; Lane, Adam; Doughman, Renee; Deutsch, Michelle; Stevenson, Charles; Stewart, Clinton; Leach, Jim; Li, Xiao-Nan; et al.
Abstract: BACKGROUND: BMI-1 is highly expressed in DIPG. Downregulation leads to inhibition of cell proliferation, cell cycle signaling, self-renewal, telomerase expression, activity, and suppression of DIPG cell migration. Targeted inhibition of BMI-1 sensitizes DIPG cells to radiation and drug-induced DNA damage. PTC596 (formulated by PTC Therapeutics, Inc.) is a novel, orally available drug that inhibits microtubule polymerization, resulting in G2/M cell cycle arrest and post-translational modification of BMI-1 protein and reduced BMI-1 protein levels. OBJECTIVES: To estimate the maximum tolerated dose and describe dose limiting toxicities, pharmacokinetics and pharmacodynamics of PTC596 in children 3–21 years of age with newly diagnosed diffuse intrinsic pontine glioma and high-grade gliomas. METHODS: PTC596 is administered twice per week orally during radiotherapy and as maintenance for up to two years. The starting dose of PTC596 was 200 mg/m 2, with a subsequent dose level of 260mg/m 2 /dose. Pharmacokinetics are performed in Cycles 1 and 2. RESULTS: This study is currently ongoing. Nine patients (7 with DIPG, 2 with HGG), 8 evaluable, have been enrolled. At dose level 1, 200 mg/m 2, three evaluable patients were enrolled and experienced no DLTs. At dose level 2, among 5 evaluable patients, 2 experienced dose-limiting grade 4 neutropenia. PTC596 has been otherwise well tolerated. Five patients remain in Cycles 2–11. CONCLUSION: This phase I trial is ongoing. PTC596 is tolerable at dose level 1. We are amending the protocol to introduce tablets that can be dissolved in liquid to allow enrollment of younger patients and those unable to swallow whole tablets.